Characteristics and Prognosis of Exercise-Related Sudden Cardiac Arrest - Toukola, Tomi M.; Kauppila, Janna P.; Pakanen, Lasse; Kortelainen, Marja-Leena; Martikainen, Matti; Huikuri, Heikki V.; Junttila, M. Juhani (Frontiers in Cardiovascular Medicine, 2018)
Introduction: The previous studies about exercise-related sudden cardiac arrest (SCA) have mainly focused on sports activity, but information related to SCA in other forms of physical exercise is lacking. Our aim was to identify characteristics and prognosis of SCA victims in the general population who suffered SCA during physical activity. Methods and results: We collected retrospectively all cases of attempted resuscitation in Oulu University Hospital Area between 2007-2012. A total of 300 cases were of cardiac origin. We only included witnessed cases with Emergency Medical System arrival time ≤15 minutes. Cases of low-intensity physical activity were excluded. A total of 47 SCAs occurred during moderate-to-vigorous physical activity (exercise-group) and 43 cases took place at rest (rest–group). The subjects in exercise-group were younger compared to the rest-group (60±14 years vs. 67±14 years, p=0.016). The initial rhythm recorded was more often ventricular fibrillation (VF) in exercise-group compared to the rest-group (77 % vs. 50 %, p=0.010). Pulseless electrical activity (PEA) was rare in exercise-group compared to the rest -group (2.1 % vs. 14 %, p=0.033, respectively). Bystander cardiopulmonary resuscitation (CPR) was more often performed when SCA took place during physical exercise (47 % vs. 23 %, p=0.020). Survival rates to hospital discharge were higher in the exercise-group compared to the rest -group (49 % vs. 9.3 %, p<0.0001). Conclusions: SCA occurring during physical activity is more frequently a result of VF and bystander CPR is more often performed. There is also a notably better survival rate to hospital discharge.